POLA ASUH AYAH (SINGLE PARENT) DALAM PENDIDIKAN ANAK KELURAHAN BANJAR SARASAN PONTIANAK TIMUR - Marasabessy, Elisa Novika; Sulistyarini, Sulistyarini; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This thesis is entitled parenting of single parent father in children’s education at RT 003 RW 004 at banjanr sarasan village eats pontianak. A common problem in this study is how to method for single pather fathers in children’s education at RT 003 RW 004 banjar sarasan village eats pontianak. The approach used in this study was to analyze the parenting style of single parents in children’s education at RT 003 RW 004 at banjar sarasan village eats pontianak. The approach used in thid study is a qualitative approach with descriptive methods data collecation techniques use interview observation techniques and connunication studies data collection tools are guidance on observation guide interviewas and documentation it is very influential on children’s learning motivation so thet there are some children who are fostered by single parent fathers do not continue their education drop out of school and the is also a child who was cared for by a single parent father to continue his education to collegaKeyword: parenting, single parent,children’s education